A crucial impact of short-range ordering on the cyclic deformation and damage behavior of face-centered cubic alloys: A case study on Cu-Mn alloys. (15th February 2021) - Han, D.; Zhang, Y.J.; Li, X.W.
Abstract: Cyclic deformation behavior and damage mechanisms of Cu-Mn alloys with high stacking fault energies (SFE) were systemically investigated at constant total strain amplitude in the range of 0.2% - 1.0% at room temperature in air. The results demonstrate that the cyclic hardening capacity and fatigue life of the alloy are notably improved with the increase of Mn content. Increasing Mn content significantly affects the damage behavior of the alloy, including a transition of cracking mode from concentrated intergranular cracking to slip band (SB)/intergranular mixed cracking and an enhanced resistance to crack propagation. All these features above are attributed to the transformation of cyclic deformation micromechanisms, i.e., the changes of slip mode from wavy- to planar-slip with increasing Mn content. The existence of short-range ordering (SRO) in Cu-Mn alloys is the essential reason for promoting slip planarity. Based on microstructural characterizations and analyses, the intrinsic connection between the SRO and the cyclic deformation and damage behavior was clarified. In brief, the present study opens another promising window to improve fatigue performance in face-centered cubic alloys especially with high SFE and SRO degree. Graphical abstract: Image, graphical abstract